Shared Bacterial and Viral Respiratory Agents in Bighorn Sheep (Ovis canadensis), Domestic Sheep (Ovis aries), and Goats (Capra hircus) in Montana - David S. Miller; Glen C. Weiser; Keith Aune; Brent Roeder; Mark Atkinson; Neil Anderson; Thomas J. Roffe; Kim A. Keating; Phillip L. Chapman; Cleon Kimberling; Jack Rhyan; P. Ryan Clarke (Veterinary Medicine International)
Transmission of infectious agents from livestock reservoirs has been hypothesized to cause respiratory disease outbreaks in bighorn sheep (Ovis canadensis), and land management policies intended to limit this transmission have proven controversial. This cross-sectional study compares the infectious agents present in multiple populations of bighorn sheep near to and distant from their interface with domestic sheep (O. aries) and domestic goat (Capra hircus) and provides critical baseline information needed for interpretations of cross-species transmission risks. Bighorn sheep and livestock shared exposure to Pasteurellaceae, viral, and endoparasite agents. In contrast, although the impact is uncertain, Mycoplasma sp. was isolated from livestock but not bighorn sheep. These results may be the result of historic cross-species transmission of agents that has resulted in a mosaic of endemic and exotic agents. Future work using longitudinal and multiple population comparisons is needed to rigorously establish the risk of outbreaks from cross-species transmission of infectious agents.